Loneliness and subjective physical health among war veterans: Long term reciprocal effects. (August 2019) - Tsur, Noga; Stein, Jacob Y.; Levin, Yafit; Siegel, Alana; Solomon, Zahava
Abstract: Rationale: Poor subjective physical health and loneliness are among the most detrimental ramifications of trauma. Indeed, substantial research has examined the link between subjective physical health and loneliness, mainly focusing on how loneliness leads to poorer physical health. However, the effects of poor subjective physical health on loneliness, as well as the reciprocal effects of these two factors, have scarcely been examined. Even less is known regarding the course of these mutual effects among individuals who have been exposed to trauma. Objective: The current investigation examines the reciprocal effects of subjective physical health and loneliness among a group of war veterans over four decades. Methods: Two-hundred and seventy-four Israeli veterans from the 1973 Yom- Kippur War reported self-rated health (SRH), somatization and loneliness at 1991 (T1), 2003 (T2), 2008 (T3) and 2015 (T4). An autoregressive cross-lagged (ARCL) modeling strategy was employed to test the bidirectional relationship between subjective health and loneliness. Results: The results showed that from T1 to T2, loneliness predicted subjective physical health. However, from T2 to T3, and from T3 to T4, subjective physical health predicted loneliness. PTSD moderated the association between loneliness and subjective physical health. Conclusion: The findings show a novel pattern of influences, demonstrating that the reciprocal effects of subjective physical health and loneliness change over time. The findings imply that subjective health and interpersonal experiences are inherently connected. Highlights: Loneliness and subjective physical health are longitudinally linked among veterans. Loneliness predicted poorer subjective physical health in the initial time-points. Subjective physical health predicted loneliness in the latter time-points.